EFFECT OF THE ATOMIC RADIUS OF ALLOYING ELEMENTS ON FORMATION OF STRAIN MARTENSITE IN BAINITIC DUCTILE IRON - Akca, Cem; Kinikoglu, Nihat G. (SPRINGER, 2011)
The effect of the atomic radius of the alloying elements (Ni, Cu, and Mo) on the rate of formation of strain-induced martensite is investigated. Since the final aim of the study is production of railway-wheel bainitic iron, a special device simulating the operation of material in a railway wheel has been constructed. Small test pieces in the form of railway wheels with different contents of Ni, Cu, and Mo were cast and subjected to isothermal hardening at 375 degrees C for obtaining a structure of upper bainite with high amount of retained austenite, which made the observation of the transformation easier. A correlation equation relating the atomic radius of the alloying element to the rate of the martensitic transformation is suggested.
Keywords: bainitic ductile cast iron; plastic deformation; martensitic transformation; Metallurgy & Metallurgical Engineering